Enhancing Public Knowledge on Sugar Consumption Limits Through Educational Games with Fuzzy Logic Implementation - Wirawan Istiono; Alexander Christian Jauwandi (IJNMT (International Journal of New Media Technology), 2026)
The creation of educational games utilising fuzzy logic to increase public awareness of Banten's daily sugar consumption restriction is predicated on the fact that there will be around 536 million instances of diabetes mellitus by 2021. By 2030, it is expected to reach 642 million. With a frequency of 10.6%, or around 19.4 million cases, Indonesia is among the top five countries in the world for the most instances of diabetes mellitus. In Indonesia, the prevalence of Banten is approximately 2.2%. An educational game is used in this study. Based on the results of the first and second pre-test quizzes, fuzzy logic will be employed in the game to calculate the player's additional time. According to the analysis's findings, of the 33 respondents, around 57,57% or 19 had increased their knowledge, whereas roughly 42,42% or 14 did not. Furthermore, the average GUESS-18 user satisfaction score is 77.84%, indicating that users "agree/satisfied" with the game. Based on the findings, it can be concluded that creating educational games with fuzzy logic to increase public awareness of Banten's daily sugar consumption limit can be an alternate method of learning